2002
DOI: 10.4236/jmmce.2002.11004
|View full text |Cite
|
Sign up to set email alerts
|

Unburned Carbon from Fly Ash for Mercury Adsorption: I. Separation and Characterization of Unburned Carbon

Abstract: In searching for a low cost adsorbent for mercury removal from flue gas, this study focuses on the utilization of unburned carbons from fly ash as the substitute material for the costly activated carbons. In this first paper of the series, various separation technologies are introduced for the extraction of unburned carbon from different sources of fly ash. The unburned carbons have been efficiently separated from clean ash, which is a value-added product for the concrete industry, with the separation technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
(4 reference statements)
1
24
0
Order By: Relevance
“…Unburnt coal particles have much higher SSA, usually between 20-60 m 2 /g [24], due to their internal porosity which is accessible to nitrogen in the BET method.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Unburnt coal particles have much higher SSA, usually between 20-60 m 2 /g [24], due to their internal porosity which is accessible to nitrogen in the BET method.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Rubel et al [137] also reported that carbon-rich products from combustion ash could decrease NOx emissions and Hg due to ion-pair interactions between NO + and O2 -at the surface of carbon, with subsequent condensation of NO2 in micropores. In addition, the pore size on the surface of the adsorbent can be changed after adsorption of a certain amount of Hg, producing the optimum pore size (micropores, < 2nm) for adsorbed NOx [138]. Rubel et al [137] also showed that the surface area of adsorbents increased due to adsorption of NOx, as shown in Figure 12.…”
Section: Nitrogen Oxidesmentioning
confidence: 85%
“…One application of CFA is used as an adsorbent [2]. CFA is composed of some oxides including Al 2 O 3 , SiO 2 having active site and unburned carbon (C) as a mesopore material [3] that enables it to act as a dual site adsorbent. On the other side, benzene is one of the toxic pollutant and carcinogenic compound [4] used as a raw material in the petrochemical industry [5].…”
Section: Introductionmentioning
confidence: 99%